Ascorbate Oxidase Induces Systemic Resistance in Sugar Beet Against Cyst Nematode Heterodera schachtii - Singh, Richard R.; Nobleza, Neriza; Demeestere, Kristof; Kyndt, Tina (Frontiers in Plant Science, 2020)
Ascorbate oxidase (AO) is an enzyme involved in catalyzing the oxidation of apoplastic ascorbic acid (AA) to dehydroascorbic acid (DHA). In this research, the potential of AO spraying to induce systemic resistance was demonstrated in the interaction between sugar beet root and cyst nematode Heterodera schachtii and the mechanism was elucidated. Plant bioassays showed that roots of AO-sprayed plants were infested by a significantly lower number of females and cysts when compared with mock-sprayed control plants. Hormone measurements showed an elevated level of jasmonic acid (JA) salicylic acid (SA) and ethylene (ET) in the roots of AO-sprayed plants, with a dynamic temporal pattern of activation. Experiments with chemical inhibitors showed that AO-induced systemic resistance is partially dependent on the JA, ET and SA pathways. Biochemical analyses revealed a primed accumulation of hydrogen peroxide (H2O2), and phenylalanine ammonia lyase (PAL) activity in the roots of AO-sprayed plants upon infection by cyst nematodes. In conclusion, our data shows that AO works as an effective systemic defense priming agent in sugar beet against cyst nematode infection, through activation of multiple basal plant defense pathways.